Efektivitas Penerapan Iklan Digital Pada Era Marketing 4.0 Di Hotel Grand Mirage Resort Bali - I Putu Esa Widahartana; I Ketut Surata; I Made Rilo Elton (JURNAL BISNIS HOSPITALITI, 2021)
The development of the industry had evolved to digital marketing, dubbed Marketing 4.0. Nowadays, the use of social media as promotional tool is important. In hospitality industry, hotels are developing their profiles on social media intensively, for example Grand Mirage Resort Bali. In 2017 the hotel finished renovating and rebranding their new wing. At the same time, the hotel cut promotional costs and focused on attracting millennial guests through digital marketing. As a result, although promotional costs were cut, promotions continued well and tended to increase. This study aimed to determine the effectiveness of implementing digital advertising at Grand Mirage Bali and how to increase the effectiveness of implementing digital advertising. Research data were collected through questionnaires and documentation studies. The collected datawere analyzed descriptively using AIDA analysis. The results showed (a) the digital advertising displayed by the Grand Mirage Resort Bali has been effective in its application as a sales promotion medium, and (b) the strategy to increase the effectiveness of the digital advertising at Grand Mirage Bali are paying attention to the message conveyed in the advertisement, using appealing visuals, choosing an ad theme that suits market conditions, and using marketing tricks such as giving limited offers.